Study of institutional policies and didactic differences in the teaching of english among first grade students of public and private schools in the distric of David, Chiriquí, 2015 - Lezcano Morales, Lesbia Leticia (UDELAS, 2015)
The study aims to analyze and compare the institutional policies of public and private schoold in the city of David. For the roles to by palyed by the administrative, teachers and students will be identified. It is also important to know: what are the academic goals for the year of the estudy? (2015)